2018
DOI: 10.1029/2018je005600
|View full text |Cite
|
Sign up to set email alerts
|

Spectral Reflectance of Powder Coatings on Carbonaceous Chondrite Slabs: Implications for Asteroid Regolith Observations

Abstract: Carbonaceous chondrite meteorites (CCs) are among the most primitive materials in the solar system and provide important insights into solar system history and evolution. A number of planetary spacecraft missions will visit asteroids that are thought to compositionally resemble these meteorites. To better assist sample acquisition in terms of how the physical properties of CCs affect their reflectance spectra, we investigated the spectral reflectance properties of solid and powdered CCs and powder coatings on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 109 publications
(197 reference statements)
4
11
0
Order By: Relevance
“…The pink arrow indicates increasing opaque abundance, and the green arrow indicates increasing particle size. dust onto slabs of the CM chondrite Murchison (Kiddell et al 2018) are similar to those observed on Bennu.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…The pink arrow indicates increasing opaque abundance, and the green arrow indicates increasing particle size. dust onto slabs of the CM chondrite Murchison (Kiddell et al 2018) are similar to those observed on Bennu.…”
Section: Discussionsupporting
confidence: 67%
“…Further, the albedo and color differences resulting from depositing varying thicknesses (113–321 µm) of dust onto slabs of the CM chondrite Murchison (Kiddell et al. 2018) are similar to those observed on Bennu.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…The red slope itself could be due to Fe-bearing oxide minerals, graphite, or both as these have been found together in some meteorites (Scott et al 1981). However, band depth and spectral slope can also be affected by factors other than abundance and composition, such as dust cover and space weathering, so the interpretation cannot be uniquely constrained (Cloutis et al 2018;Kiddell et al 2018).…”
Section: Discussionmentioning
confidence: 99%
“…[32]), asteroidal (e.g. [28]), or planetary surfaces (e.g. [4]), and also in the study of organic cells in biology (e.g.…”
Section: Introductionmentioning
confidence: 99%